Auditoria de gestión a los departamentos de crédito y cartera del banco Pichincha, agencia Buena Fe, año 2011 - Sabando Cedeño, Martha Elizabeth (2013)
This research aims to develop critical Auditing the Credit Department and Agency Portfolio of Banco Pichincha Good Faith The development and implementation of the study did in Banco Pichincha Agency Facilities Buena Fe, located at Av August 7 and V. Rocafuerte Corner, which aimed General conduct an audit of the Department of Management and Portfolio Credit regarding the rules and procedures applied and how these affect the staff's actions regarding the qualification, approval and loan recovery allocated during 2011. For the fulfillment of the proposed objectives, a structured audit plan according to the following phases: Phase I Preliminary Planning, Audit Planning Phase II, Phase III and Phase IV Execution communication results, which proved that there are no situations yielded higher danger, since the rate reported by the Bank portfolio is among the acceptable levels. An important factor that affects the normal development of the Credit Department staff is that it must perform two activities simultaneously Gestiones placement and recovery, being affected the second and more important personnel placement gives it to recovery which impacts directly on the timely recovery of the commercial portfolio especially since increased delinquencies recorded mainly limited monitoring that give Advisors.